Mapping and Identification of Antifungal Peptides in the Putative Antifungal Protein AfpB from the Filamentous Fungus Penicillium digitatum - Garrigues, Sandra; Gandía, Mónica; Borics, Attila; Marx, Florentine; Manzanares, Paloma; Marcos, Jose F. (Frontiers in Microbiology, 2017)
Antifungal proteins (AFPs) from Ascomycetes are small cysteine-rich proteins that are abundantly secreted and show antifungal activity against non-producer fungi. A gene coding for a class B AFP (AfpB) was previously identified in the genome of the plant pathogen Penicillium digitatum. However, previous attempts to detect the AfpB protein were not successful despite the high expression of the corresponding afpB gene. In this work, the structure of the putative AfpB was modeled. Based on this model, four synthetic cysteine-containing peptides, PAF109, PAF112, PAF118 and PAF119, were designed and their antimicrobial activity was tested and characterized. PAF109 that corresponds to the γ-core motif present in defensin-like antimicrobial proteins did not show antimicrobial activity. On the contrary, PAF112 and PAF118, which are cationic peptides derived from two surface-exposed loops in AfpB, showed moderate antifungal activity against P. digitatum and other filamentous fungi. It was also confirmed that cyclization through a disulfide bridge prevented peptide degradation. PAF116, which is a peptide analogous to PAF112 but derived from the Penicillium chrysogenum antifungal protein PAF, showed activity against P. digitatum similar to PAF112, but was less active than the native PAF protein. The two AfpB-derived antifungal peptides PAF112 and PAF118 showed positive synergistic interaction when combined against P. digitatum. Furthermore, the synthetic hexapeptide PAF26 previously described in our laboratory also exhibited synergistic interaction with the peptides PAF112, PAF118 and PAF116, as well as with the PAF protein. This study is an important contribution to the mapping of antifungal motifs within the AfpB and other AFPs, and opens up new strategies for the rational design and application of antifungal peptides and proteins.